Will of entrustment as a means of protection of the child’s right to property in Islamic law - Ibrahim, Badruddin (2012)
Children are the future of a Nation. Due to vulnerability, they require protection in many aspects of their life. Parents are main supporters and sustainers of the children during their lifetime. After their death, their property left for their children may provide a continuous financial support for the children maintenance, education and welfare. The issue arises as to the protection and administration of the property, as children due to their deficiencies, are not able to manage them wisely. If a qualified person is not appointed to carry out the task, it will lead to misappropriation and embezzlement of property. Therefore, in order to protect the children’s rights to property, it is very significant to appoint a person as a trustee, so that the children’s property may be properly safeguarded and administered. This paper seeks to examine means of protection of child’s right to property after the death of his parents in Islamic law through the instrument of will of entrustment (al-wisoyah). Examination extends to the provision of Islamic law in Malaysia which serves as a comparison. The research is basically a library research, undertaken on the premise that Islamic law has mechanism of providing a solution for protection of the child’s right to property after the death of his parent.